Electricity deregulation: choices and challenges. - Griffin, James M.; Puller, Steven L. (Bush School series in the economics of public policy ; |v v. 4, 2005)
The electricity market has experienced enormous setbacks in delivering on the promise of deregulation. In theory, deregulating the electricity market would increase the efficiency of the industry by producing electricity at lower costs and passing those cost savings on to customers. As Electricity Deregulation shows, successful deregulation is possible, although it is by no means a hands-off process—in fact, it requires a substantial amount of design and regulatory oversight. This collection brings together leading experts from academia, government, and big business to discuss the lessons learned from experiences such as California's market meltdown as well as the ill-conceived policy choices that contributed to those failures. More importantly, the essays that comprise Electricity Deregulation offer a number of innovative prescriptions for the successful design of deregulated electricity markets. Written with economists and professionals associated with each of the network industries in mind, this comprehensive volume provides a timely and astute deliberation on the many risks and rewards of electricity deregulation.